2021
DOI: 10.3389/fnagi.2021.674288
|View full text |Cite
|
Sign up to set email alerts
|

Right Frontoinsular Cortex: A Potential Imaging Biomarker to Evaluate T2DM-Induced Cognitive Impairment

Abstract: Cognitive impairment in type 2 diabetes mellitus (T2DM) is associated with functional and structural abnormalities in the intrinsic brain network. The salience network (SN) is a neurocognitive network that maintains normal cognitive function, but it has received little attention in T2DM. We explored SN changes in patients with T2DM with normal cognitive function (DMCN) and in patients with T2DM with mild cognitive impairment (DMCI). Sixty-five T2DM patients and 31 healthy controls (HCs) underwent a neuropsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…We scrutinized references in studies that have not been ruled out, seven more references were found that met the criteria for inclusion. We excluded 69 studies after reading the full text because six studies had serious complications ( 51 56 ), eight studies had no healthy controls ( 57 64 ), 28 studies had ROI analyses only ( 65 92 ), nine studies were methods of brain structural analysis ( 93 101 ), nine studies did not report coordinates ( 102 110 ) (sent to the author for help, no results), the data used in the two studies are the same as the articles included in this study ( 111 , 112 ), and seven studies had a quality score of less than 17 ( 113 119 ). The final meta-analysis included 23 eligible trials with 27 data sets ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We scrutinized references in studies that have not been ruled out, seven more references were found that met the criteria for inclusion. We excluded 69 studies after reading the full text because six studies had serious complications ( 51 56 ), eight studies had no healthy controls ( 57 64 ), 28 studies had ROI analyses only ( 65 92 ), nine studies were methods of brain structural analysis ( 93 101 ), nine studies did not report coordinates ( 102 110 ) (sent to the author for help, no results), the data used in the two studies are the same as the articles included in this study ( 111 , 112 ), and seven studies had a quality score of less than 17 ( 113 119 ). The final meta-analysis included 23 eligible trials with 27 data sets ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The insula is involved in emotional recognition and processing, cognition and motivation 64 . Altered insular gray matter volumes occur in patients with type II diabetes and are associated with increased anxiety and depression 65 as well as cognitive impairment 66 . Importantly, insulin resistance moderates the relationship between childhood abuse and insula-precuneus connectivity in depressed and overweight youth 67 ..…”
Section: Discussionmentioning
confidence: 99%
“…Integrity of the SN is necessary for the efficient regulation of flexibly coupling either with the DAN or DMN networks during different brain states, and that a failure of this regulation leads to attentional lapses and other inefficient cognitive control (Bonnelle et al, 2012). Our previous studies have shown that there are abnormal changes in the SN of patients with T2DM under different cognitive stages, the right frontoinsular cortex (the core region of the SN) may be a useful imaging biomarker for supplementary assessment of early cognitive dysfunction in patients with T2DM (Zhang et al, 2021). This study found the anti-correlation between DAN and DMN showed disease-related disruptions in patients with T2DM.…”
Section: Altered Anticorrelation Between the Default Mode Network And Dorsal Attention Networkmentioning
confidence: 99%